Noodzaken ! : een kollektie jonge kunst... (Turnhout : Kokatoe, 1985)
Bogaerts, Marc ; Bosmans, Peter ; Maes, Herman ; Daems, Walter ; Carlier, Jan ; Castelein, Ingrid ; Coucke, Jo ; De Roover, Marc ; Devriendt, Robert ; Fierens, Kris ; Geryl, Bavo ; Ghekiere, Joris ; Haveman, Nina ; Huybrechts, Jo ; Maes, Herman ; Morez, Paul ; Opdebeeck, Bart ; Peters, Willy ; Riemis, Pool ; Tordoir, Narcisse ; van Bergen, Thé ; Plaetsen, Wim Van der ; Vandevelde, Ludwig ; Van Gestel, Fik ; Van Soom, Luk ; Verbist, Carlo ; Verdin, Walter ; Wagemans, Frank ; Daems, Walter
biog. [1 p. per kunstenaar]
Nederlands
Noodzaken !, Kokatoe, Turnhout, VI/VII tot IV/VIII MCMLXXXV (1985)
kunstcatalogus